Adsorption and Ionization of Carboxylic Acids at the Air/Water Interface - Badban, Shiva (Curtin University, 2017)
Surfactants are widely used in our daily life from pharmaceuticals and washing products to petroleum and biotechnology. Despite of thousands years of applications, the ionization of surfactants at the air/water interface is still unquantified. This study focuses on ionic surfactants performance at air/water interface. Carboxylic acids of C9 and C10 were investigated experimentally and theoretically. Finally, adsorption parameters obtained from this work shred important insights into ionization of fatty acids at the air/water interface.